The Influence Of Health Education On Safe Delivery On The Motivation Of Membership In The Health Facility - Rhoma Diana; Septika Yani Veronica (Chakra Brahmanda Lentera Institute, 2022)
Background: The high rate of MMR and AKN in Bangkunat District is one of the causes of deliveries not in health facilities. The low coverage of deliveries in health facilities is 64.66% of the 100% target in 2020, one of which is caused by the lack of knowledge of pregnant women about the importance of giving birth in health facilities. This study aimed to determine the effect of health education on safe delivery on motivation to give birth in health facilities in the Public Health Center working area. Bengkunat Belimbing Health Center in 2021. Method: The design in this study was pre-experimental (the one group pretest-posttest without control group design). The population in this study were all pregnant women in the third trimester in Pekon Pendingan, Pekon Jawa City, Pekon Pemerihan, Pekon Sumberejo, and Pekon Sukanegeri, totaling 31 pregnant women in the third trimester. The sample was taken from as many as 31 third-trimester pregnant women given counseling about safe delivery. Bivariate analysis in this study used a Parametric, namely the Paired Sample T-Test. Result: Test Parametric (Paired Sample T-Test) obtained a p-value of 0.000 (<0.01), which means that there is an effect of health education on safe delivery on motivation to give birth in health facilities in the Public Health Center work area. Bengkunat Belimbing Public Health Center in 2021. Conclusion: Based on the results of the study, the researchers suggest that it is necessary to strengthen the implementation of health education regarding safe delivery to pregnant women both in quantity and quality, which is carried out in Posyandu, maternal classes, or in health facilities by ensuring that all pregnant women have been given education health, monitoring the implementation of health education activities as well as the implementation of technical guidance activities on an ongoing basis.